Effectiveness of low permeability concrete in waterproofing basement walls and concrete floor slabs - Romantico, Hannah Grace S.
The major factors that affect structural integrity can be traced back to the presence of water in the structure. Thus, to maintain the structural integrity of buildings with basements, waterproofing basement walls and concrete floor slabs is important. There are several existing methods of waterproofing concrete, but the possibility of utilizing concrete itself to waterproof the structure has not been extensively investigated yet. Admixtures such as pozzolanic fly ash, silica fume and a commercially available waterproofing compound are proven to be have the ability to reduce permeability of concrete. However, there has been no current research that studied the effectiveness of these admixtures relative to each other. This research aims to observe the effect of admixture on water permeability of concrete, and to determine if the admixtures can reduce the appearance of cracks. Results indicate that among the three admixtures tested, concrete with silica fume yielded the lowest coefficient of permeability, having an average k of 7.5236E-11 m/s for 28-day cured samples and a k of 4.1408E-11 m/s for 56-day cured samples. Moreover, silica fume managed to increase the compressive strength by 34.3%, flexural strength by 34.3%, split tensile strength by 15.7% compared to the control set-up after 56 days of curing. It also reduced the shrinkage of concrete to only 0.016%. Consequently, it can be surmised that silica fume decreases the occurrence of structural and shrinkage cracks in concrete. In addition, it was observed that there is an inverse relationship between the coefficient of permeability of concrete and its compressive strength, flexural strength, split tensile strength, with each having a Pearson r correlation factor of -0.9895, -0.9834 and -0.9942, respectively. However, there is no significant relationship between coefficient of permeability of concrete and its drying shrinkage, having a Pearson r correlation factor of only 0.026. Also, the study was able assess the economic feasibility of the tested admixtures by comparing their cost of production. Even if silica fume has a higher unit price in the market, the use of silica fume in integral waterproofing is promising. Utilizing silica fume in integral waterproofing may decrease the required thickness needed in waterproofing membranes or may even be totally eliminated once the mix is improved.